FINANCIAL CRISIS: ILLUSION OF SUPPRESSION - Yu. S. Begma; E. V. Zenkina (Вестник университета, 2019)
It has been shown, that the financial crises in the last twenty years intensified attempts to rethink the dominant neo-liberal concepts of globalization of monetary and credit relations. Achievements of financial technology allowed to overcome some arising problems and generated hopes for a possibility of preservation of a former paradigm of market capitalism and regularities of globalization of world economy. However, a more detailed consideration of new developments in the field of international monetary and financial relations leads to the conclusion, that such hopes are illusory.